Statistically order continuous operators on Riesz spaces - Aydin, Abdullah; Gorokhova, Svetlana; Selen, Ramazan; Solak, Sumeyra (Maejo Univ, 2023)
Some kinds of statistical convergence have been studied and investigated on Riesz spaces with respect to order convergence recently. In this paper we introduce the concept of statistically continuous and bounded operators with statistically order convergent sequences on Riesz spaces. Moreover, we give some relations with other kinds of operators.
Keywords: Vector Lattice; Statistically Continuous Operator; Statistically Bounded Operator; Statistical Order Convergence; Convergence